1597d Participatory ergonomic programs in commercial construction projects: engagement with multiple organisational levels to improve effectiveness. (24th April 2018) - Dale, AM; Welch, L; Evanoff, BA
Abstract : Introduction: Effective participatory ergonomic programs require cooperative engagement of management and workers to identify hazardous tasks and implement useful solutions. We report findings from participatory programs within seven single employers on different multi-employer construction projects. Methods: We trained all employees in ergonomic principles, hazard recognition, and use of a participatory approach to identify and implement feasible solutions. We measured program delivery and effectiveness through training records, number of identified hazardous tasks and solutions, and number of employer-controlled and worker-controlled solutions implemented over a three-month period. Result: Most (91%) of the 95 workers were trained; participating workers identified 105 hazardous tasks. Equipment solutions for 43 of these tasks were the responsibility of the employer; workers were responsible for 44 tool and 8 work practice solutions. Ten hazardous tasks without solutions related to the construction environment and/or schedule that were controlled by the primary contractor. Relatively few employer-controlled equipment solutions (33%) were implemented during the project while 75% of the worker-controlled tool solutions were implemented. Discussion: These results highlight two barriers to implementing effective solutions in single employer participatory ergonomic programs: employers do not involve workers in selecting useful equipment for projects, and primary contractors control the project schedule and environment. The complex organisation of multi-employer sites and frequently changing work tasks and environments may account for the varied effectiveness of participatory ergonomic programs in construction. Most programs have engaged workers within single employers, rather than being integrated within the overall construction management processes overseen by a primary contractor. A new study is underway that integrates ergonomic training, planning, and oversight within the primary contractor's safety programs, and encourages planning to reduce ergonomic hazards during the preconstruction phase.